An overview of electrification rural areas in Palestine by using micro-grid solar energy - Imad H. Ibrik (Taylor & Francis Group, 2019)
Palestine has a large number of rural areas which have no electricity services and cannot be connected to local grid in the near future for political and financial obstacles. This paper present the techno-economic impact of electrification of small communities by using micro-grid photovoltaic (PV) systems, and also reduction in CO2 emission in comparison to using diesel generator which causes high rates of environmental pollution will be analyzed. The implemented two micro-grid PV systems for electrification two communities in Palestine will cover the electricity needs of households and street lighting and can replace traditional unsustainable energy sources. Also, micro-grid PV systems have positive impacts on people’s health and on the environment besides economic and social benefits.